The drunkard's walk how randomness rules our lives - Mlodinow, Leonard 1954- (Pantheon Books, 2008)
An irreverent look at how randomness influences our lives, and how our successes and failures are far more dependent on chance events than we recognize.
Includes bibliographical references and index
Keywords: Random variables; Probabilities; Chance; Wahrscheinlichkeitsrechnung